A soy-based product fermented by Enterococcus faecium and Lactobacillus helveticus inhibits the development of murine breast adenocarcinoma - Lopes Kinouchi, Fernanda (2012)
Purpose: Soy and its fermented products are considered functional foods. The study objective was to assess three functional food - a non-fermented soy product (NFP), fermented soy product (FSP), fermented soy product enriched with isoflavones (FI) - in terms of their ability to reduce the development of adenocarcinoma in mice, as well their ability on modulating immune system. Methods: It was observed tumor volume and to verify correlations with the immune system it was measured levels of the cytokines IL-1β and TNF-α produced by macrophages as well as IFN-γ produced by lymphocytes using ELISA test, and nitric oxide production by macrophages using Griess reagent. Results: All products showed immunological activity, but FSP showed the most effective tumor containment, resulting in smallest tumor volumes. FI animals expressed larger amounts of nitric oxide and IL-1β and exhibited larger tumor sizes than FSP and NFP animals. Conclusions: The results suggested that the ingestion of FSP was most efficient in tumor containment, possibly due to a positive modulation of the immune system by when Enterococcus faecium and Lactobacillus helveticus are added to the soy product.